Nutritional rickets in three toddlers during Covid-19 pandemic lockdown - Lee, Yee Lin; Yusoff, Nor Azyati; Ting, Tzer Hwu (International Islamic University Malaysia, 2022)
Nutritional rickets is a worldwide problem which has been increasingly reported globally. Three toddlers aged 1-2 years presented in March to April 2021 with bony deformities following one year of national Covid-19 pandemic lockdown since March 2020. All three patients were breastfed till presentation without formula milk supplementation. Weaning occurred at 4-6 months of age but without proper complementary food intake. All three patients and their nursing mothers were mostly confined indoors during the pandemic lockdown. Bone metabolic profile and radiological imaging confirmed vitamin D deficiency rickets. All three patients responded well to vitamin D3 treatment and calcium supplementation for 3-6 months duration. Vitamin D deficiency rickets appears to be an increasing problem in breastfed toddlers following the prolonged movement control order, particularly amongst picky eaters and young children on restrictive diets. Sun exposure and early vitamin D supplementation are crucial to prevent the development of nutritional rickets.